Guerra, impero, rivoluzione: Russia, 1914-1917 War, Empire, Revolution: Russia, 1914-1917 - Giovanna Cigliano (Clio: Saggi di scienze storiche, archeologiche e storico-artistiche, 2018)
The dramatic involvement of the Tsarist Empire in the First World War marks a turning point in the history of Russia and its surrounding areas. The dynamics triggered by the challenge of total mobilization gave rise to political, social, economic and cultural transformations destined to have a profound and prolonged impact on Europe and the whole world during the 20-th century. The studies and the researches collected in this volume explore key themes of the crisis that hit the imperial space: the patriotic culture and the representation of the enemy in war propaganda; the interweaving of war effort and national issues in the imperial peripheries; the intensified competition between the multiethnic empires in the context of total war; the breakthrough achieved by nationalisms during the 1917 revolutions. Special attention is also devoted to the analysis of the international historiographical trends that have emerged in the last quarter of a century and which have redefined the interpretation of the period 1914-1921 / 22.